Changes induced by recreational and educational activities in children with diabetes - Mercuri, Nora (2009)
Children with diabetes face numerous daily challenges that are completely different from those of other children their age. Dealing with those issues successfully requires that children with diabetes and their families acquire knowledge and develop skills and attitudes to overcome those challenges through a process of continuous education. Such a process simultaneously promotes the development of healthy behavioral changes and the consequent active and effective participation in the control and treatment of the disease. Therapeutic education should start at diabetes diagnosis and should include the child and family members. Contents, pedagogical methodology, language, and didactic material should adapt to the age and maturity of the child. Psychosocial, cultural, and economic factors should also be considered to achieve the therapeutic and educational goals. In this educational context, residential camps for children and youth with diabetes worldwide16-25 appear to be a suitable education strategy because 1) the teaching-learning process is enhanced by a recreational, motivating, and safe environment; 2) the presence of other children and staff members with diabetes give them the opportunity to be in the majority and not an exception; 3) formal education sessions are accompanied by observation, imitation, practice, and exchange of opinions and experience; 4) group creative and innovative didactic methods are useful to convey and consolidate knowledge, self-management, and problem-solving skills concerned with diabetes control instead of the traditional passive attitude of the unidirectional educational model; and 5) children and their families have the opportunity to integrate and exchange experiences about living with a chronic disease. Evidence in the literature has demonstrated the positive effect of camps for children and youth with diabetes on their specific knowledge, self-management skills, and self-esteem. However, only a few studies have reported their clinical and metabolic benefits in the post-camp period. Therefore, the aim of this study was to evaluate in campers the effect of educational activities on diabetes knowledge, self-management skills, and glycemic control during and after the camp and in family members how the implementation of post-camp activities affects their knowledge about diabetes control and treatment.